Optimal size of plots for experiments with in vitro establishment of species of the passiflora genus (Research, Society and Development, 2020)
The genus Passiflora have great commercial, ornamental and phytotherapeutic importance. However, information on the ideal plot size in experiments aiming at the in vitro establishment of Passiflora is scarce. This study aimed at determining the optimal size of plots in experiments of in vitro establishment of the species Passiflora edulis Sims f. edulis, Passiflora giberti N. E. Brown. and Passiflora laurifolia L. For each species, uniformity tests were conducted with two concentrations of salts of the culture medium (MS and ½ MS) and for each test, evaluations were performed at 45, 75 and 105 days after incubation of the explants. In each evaluation and culture medium, different sizes of plots were simulated, ranging from one (1) basic unit to 50 per plot, with each basic unit consisting of a plant. To estimate the optimum plot size, the modified maximum curvature method was used. In in vitro establishment experiments, the recommended optimal plot size should be 11 explants for P. edulis Sims f. edulis, of 15 explants for P. giberti N. E. Brown. and 9 explants for P. laurifolia L.